The Long Noncoding RNAs NEAT1 and MALAT1 Bind Active Chromatin Sites - West, Jason A.; Davis, Christopher P.; Sunwoo, Hongjae; Simon, Matthew D.; Sadreyev, Ruslan I.; Wang, Peggy I.; Tolstorukov, Michael Y.; Kingston, Robert E. (Molecular cell, 2014)
Mechanistic roles for many lncRNAs are poorly understood, in part because their direct interactions with genomic loci and proteins are difficult to assess. Using a method to purify endogenous RNAs and their associated factors, we mapped the genomic binding sites for two highly expressed human lncRNAs, NEAT1 and MALAT1. We show that NEAT1 and MALAT1 localize to hundreds of genomic sites in human cells, primarily over active genes. NEAT1 and MALAT1 exhibit colocalization to many of these loci, but display distinct gene body binding patterns at these sites, suggesting independent but complementary functions for these RNAs. We also identified numerous proteins enriched by both lncRNAs, supporting complementary binding and function, in addition to unique associated proteins. Transcriptional inhibition or stimulation alters localization of NEAT1 on active chromatin sites, implying that underlying DNA sequence does not target NEAT1 to chromatin, and that localization responds to cues involved in the transcription process. [Display omitted] •High-resolution genomic binding sites for the human lncRNAs NEAT1 and MALAT1•NEAT1 and MALAT1 exhibit distinct colocalized binding at active chromatin•Transcription impacts NEAT1 localization patterns•CHART-MS identifies proteins associated with endogenous RNAs in vivo NEAT1 and MALAT1 are two of the most abundant mammalian lncRNAs. West et al. map the genomic binding of NEAT1 and MALAT1 and identify interacting proteins via RNA pull-down followed by mass spectrometry, showing these RNAs play a synergistic role in nuclear organization linking active genes and nuclear subdomains.